Etnicidade e Representações sobre Doenças entre as Etnias Indígenas da Cidade de Uaupés (Alto Rio Negro, AM) - Observações Referenciais sobre Tuberculose e Haseníase - Gomes, Daniele Moreira (Museu Paraense Emílio Goeldi, 2023)
The health/illness conditions of Brazilian indigenous societies, throughout our history, have been the object of numerous approaches, and public and institutional policies. Studies in this field need to take into account the social organization, cosmology, and conception of health, disease, healing, body, death, and the supernatural in these societies. This study seeks to analyze the representations about diseases and health/illness problems among ethnic groups in the city of Uaupés, especially about tuberculosis and leprosy, and the repercussions and consequences that such problems have on family dynamics and people's daily lives. We adopted as a research base the bibliographic and documental studies on the subject, visits to institutions and health professionals, and field observations in the Alto Rio Negro region, Amazonas. The indigenous ethnic groups represent 70% of the local population studied, and their conceptions about health/disease are related to supernatural entities and are also part of a struggle imposed by the situation of contact with the national society. We followed up two indigenous patients with tuberculosis, taking into account their family network, therapeutic itinerary, access to health services, resistance and difficulties of treatment and its possible effectiveness. In contrast to the evidence of tuberculosis in the study site, the presence of leprosy is still being observed in the present research. The city of Uaupés (São Gabriel da Cachoeira) in the last decade took a leap in urban expansion and dynamization in the tertiary sector, emerging as another emerging Latin American city. This crucial moment determines the need for compatible public policies regarding indigenous health